Pengaruh Etika Bisnis Terhadap Keberlanjutan Usaha Mikro Kecil dan Menegah (UMKM) di Surabaya - Leba, Desinta; Sandari, Tries Ellia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Business ethics are an important element in maintaining business sustainability, especially in MSMEs which are a vital sector in the Indonesian economy. This study aims to analyze the influence of business ethics on the sustainability of MSMEs in Surabaya. The research method uses a quantitative approach with survey techniques to MSME actors in various business sectors. The research instrument is in the form of a questionnaire with a Likert scale that measures the dimensions of business ethics such as honesty, transparency, fairness, and responsibility, as well as business sustainability indicators such as operational stability, customer loyalty, and business growth. Data analysis uses simple linear regression. The results of the study are expected to show that business ethics have a positive and significant effect on the sustainability of MSMEs in Surabaya. These findings confirm that the implementation of business ethics is not only a moral obligation, but also an important strategy in the development of a long-term oriented business. Business ethics are a fundamental pillar in maintaining business sustainability, especially for Micro, Small and Medium Enterprises (MSMEs) which have a strategic role in the national economy. In the context of increasingly fierce competition and ever-evolving consumer demands, the application of business ethics serves not only as a moral guideline, but also as a strategy to improve reputation and competitiveness. Various studies show that business ethics can reduce business risks, increase customer trust, and strengthen the company's position in the long term. This is increasingly relevant for MSMEs in Surabaya which is the center of creative economy and trade activities in eastern Indonesia. In addition, several articles highlight the importance of business ethics in facing the era of digitalization. The application of ethics in digital media, online marketing, and electronic transactions is an important factor that determines the sustainability of modern MSME businesses. Articles related to the digital economy show that MSME actors who adopt technology without ignoring business ethics tend to perform better, especially in terms of increasing customer loyalty and the effectiveness of marketing strategies. This is in line with the dynamics of MSMEs in Surabaya which are increasingly shifting towards a digital-based business ecosystem.